2013
DOI: 10.3109/10903127.2012.749964
|View full text |Cite
|
Sign up to set email alerts
|

Muscles Used for Chest Compression Under Static and Transportation Conditions

Abstract: Chest compression is performed mainly through flexion and extension of the hip joint while kneeling on the floor and through the elbow and shoulder joints while standing in a moving ambulance. Therefore, the low quality of chest compression during ambulance transportation may be attributable to an altered technique of performing the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…During CPR practise, triceps brachii plays an important role in extending the elbow [ 17 ], whereas rectus abdominis controls the trunk and stabilizes the upper body to provide a proper force distribution during chest compressions [ 6 ]. For this reason, contractile properties of these muscles were measured through non-invasive and non-demanding TMG in this study.…”
Section: Discussionmentioning
confidence: 99%
“…During CPR practise, triceps brachii plays an important role in extending the elbow [ 17 ], whereas rectus abdominis controls the trunk and stabilizes the upper body to provide a proper force distribution during chest compressions [ 6 ]. For this reason, contractile properties of these muscles were measured through non-invasive and non-demanding TMG in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013 in Japan, Yasuda et al 9 conducted a study to illustrate the different muscles used when performing chest compressions while kneeling on the floor and standing in a moving ambulance. They concluded that the low quality of chest compressions in ambulance may be attributed to an alteration of the technique of performing chest compressions.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate (HR) was measured at rest, during chest compression, and during recovery using a Life Scope 8 (Nihon Kohden Co., Tokyo, Japan). During chest compressions, the surface EMG collected data from the triceps brachii, deltoid, trapezius, erector spinae, external oblique muscle, rectus femoris, biceps femoris, and medial gastrocnemius muscles using SX230‐1000 electrodes (Biometrics Ltd., UK) (Trowbridge et al, ; Yasuda et al, ). The electrodes were attached to the belly of each muscle, and the skin was abraded and cleaned with alcohol before attachment to minimize impedance.…”
Section: Methodsmentioning
confidence: 99%